Dampak Kehadiran Guru Di Kelas Terhadap Kedisiplinan Siswa Dalam Proses Pembelajaran Di Upt Sdn Laiyolo No. 52 Kepulauan Selayar - Ahry Ramadhani (Harmoni: Jurnal Ilmu Komunikasi dan Sosial, 2023)
This study aims to determine the impact of teacher presence in class on student discipline in the learning process at UPT SDN Laiyolo No. 52 Selayar Islands The research method used is qualitative research. In this study the data collection techniques used included direct observation and interviews. Based on observations made, the effect of the teacher’s presence in class on student discipline in the learning process is still unsatisfactory based on the observations I have made for the past 3 months. Where these activities can be seen from teacher’s who are lazy to teach, teacher’s who are lazy to come to scholl and even come late to school. So that little the students are also lazy to go to school because they feel less enthusiastic about participating in learning. The results of the research that can be found are that the presence of the teacher greatly influences student discipline in the learning process at school. In order to from a disciplined and obedient nature, it is therefore important for a teacher to be present in every phase of the development of students in every lesson. Teacher’s also have to be a good example for their student.